Liberal perfectionism : the reasons that goodness gives - Couto, Alexandra, 1978- (Practical philosophy., 2013)
Literature on political perfectionism has often mainly focused on dealing with objections. This book highlights the intuitive appeal of liberal perfectionism. Many objections to perfectionism are shown to fail to reach their target once appropriate distinctions are drawn and a plausible form of liberal perfectionism is endorsed. More surprisingly, Couto suggests that perfectionism might be compatible with the concept of social justice.